Analyse Large Storage Network Technologies: Exploring Tools and Technologies for Large Storage Networks (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Multi path connectivity allows multiple IP addresses to associate with a network interface. Multipath provides continued access to storage even if a storage fabric component fails. Some important tools to resolve fiber channel network issues include I. e Name server, fcping, Rescan, and port error counters.